Agência educacional no âmbito da educação básica de São Paulo: caracterização e análise de contingências no período pós-pandemia - Neumann, Matheus Marques (2023)
The Basic Education schools in the public education network of the State of São Paulo are guided by directives from the Secretaria de Educação de São Paulo (SEDUC/SP), including the schools participating in the Programa de Ensino Integral (PEI). Such schools operate under the prescriptions of SEDUC/SP, which direct demands to be fulfilled by the professionals working within them. In the year 2021, a complete return to in-person regular classes took place in São Paulo state schools after the onset of the COVID-19 pandemic. The research focus of this work consisted of identifying, describing, and analyzing the relationships established between SEDUC/SP, the school administration, and the pedagogical coordinators. The concept of Controlling Agencies, initially described in "Science and Human Behavior" written by Skinner in 1953, was adopted.This dissertation aimed to investigate the extent to which the contingencies reported in the functioning of a PEI-mode school unit replicate features of control and countercontrol relationships, such as the use of predominantly punitive and minimally instructive procedures that generate behaviors of obedience, or countercontrolling behaviors such as escape and resistance, at the intersection between the governmental and educational control agencies. Three interviews were conducted with the principal and general coordinator together, one interview with the Math subject coordinator, and one interview with the Portuguese Language subject coordinator. The interviews were transcribed verbatim, followed by a comprehensive analysis of the material. Categories encompassing the actions developed by the PEI school, the pandemic context, and the mitigation actions during this period, as well as the context of external evaluations proposed by SEDUC, and the detailed description of one of the PEI school's actions called the "Leveling Action Plan," were proposed based on thisanalysis. Subsequently, both general and specific contexts were outlined for the actions developed by the school, to elucidate the potential control exerted by SEDUC/SP over the actions carried out by the professionals of the school unit. The reports indicate that a significant portion of the pedagogical management actions, although showing adherence and subordination to the official directives of SEDUC/SP, clearly demonstrate adjustments and adaptations in complying with official guidelines that are under the influence of considering and recognizing the characteristics of the repertoires of teachers and students within the school unit. Thus, despite the control relationships that materialize the administrative linkage of the reported actions with the orientations and directives of SEDUC/SP, the reports describe actions of the school unit that seem to document an autonomous approach in pedagogical management which, by prioritizing the dimensions and characteristics of teachers and students, fill in the gaps and deficiencies described in the ways of expression of control by SEDUC/SP. Concurrently, these actions also realize initiatives that can be interpreted as forms of counter control exercised within the school unit about the governmental agency